Biophysical and Biochemical Markers of Metal/Metalloid-Impacts in Salt Marsh Halophytes and Their Implications - Anjum, Naser A.; Duarte, Bernardo; Caçador, Isabel; Sleimi, Noomene; Duarte, Armando C.; Pereira, Eduarda (Frontiers in Environmental Science, 2016)
As a major sink, estuarine/salt marsh ecosystem can receive discharges laden with myriads of contaminants including metals/metalloids from man-made activities. Two among the major consequences of metal/metalloid-exposure in estuarine/salt marsh ecosystem flora such as halophytic plants are: (a) the excessive accumulation of light energy that in turn leads to severe impairments in the photosystem II (PS II), and (b) metal/metalloids-accrued elevation in reactive oxygen species (ROS) in cells that causes imbalance in cellular redox homeostasis. On one hand, plants adopt several strategies to dissipate excessive energy hence eventually to avoid damage in the PS II and maintain optimum photosynthesis. On the other hand, components of cellular redox system quickly respond to metal/metalloid exposure, where plants try to maintain a fine-tuning therein and tightly control the level of ROS and its potential consequences. Based on recent reports this paper: (a) overviews in separate sections major insights into and the significance of major biophysical and biochemical markers in metal/metalloid-exposed halophytes; and (b) concludes the paper and highlights major points so far unexplored in the current context. Discussion reflects the need of integrating studies on major biophysical and biochemical markers in order finally to unveil tolerance/resistance mechanisms in halophytes under metal/metalloid exposed conditions.